ANALISIS FAKTOR YANG MEMPENGARUHI TERJADINYA FINANCIAL STATEMENT FRAUD: PERSPEKTIF FRAUD HEXAGON THEORY (Studi Empiris Pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018–2020) - Kiki Elita Septiningrum; Siti Mutmainah (Diponegoro Journal of Accounting, 2022)
The importance of the information contained in financial statements often makes management commit fraudulent practices through earnings management so that the reports presented look attractive to stakeholders. The purpose of this study was to analyze the factors in the occurrence of financial statement fraud with the perspective of the fraud hexagon theory proposed by Vousinas (2017) consisting of six indicators, namely pressure, opportunity, rationalization, capability, arrogance and collusion. The six indicators cannot be measured directly so they are proxied through the variables of financial stability, ineffective monitoring, auditor switch, change of director, frequency number of CEO's picture and political connections. The population of this study consists of all financial companies that were listed on the Indonesia Stock Exchange between 2018–2020. The sampling method used was purposive sampling technique  and obtained a sample of 43 companies with 129 data. The type of data used is secondary data from annual companies report.       The results of this study show that financial stability and auditor switch have a significant positive effect on financial statement fraud. Meanwhile, the frequency number of CEO's picture has a significant negative effect on financial statement fraud. Ineffective monitoring, change of directors, and political connections variables do not affect on financial statement fraud.